1997
DOI: 10.2307/1511092
|View full text |Cite
|
Sign up to set email alerts
|

Risk, Resilience, and Adjustment of Individuals with Learning Disabilities

Abstract: This article uses the concepts of risk and resiliency to frame our understanding of how having a learning disability affects nonacademic outcomes such as emotional adjustment, family functioning, adolescent problems of school dropout, substance abuse and juvenile delinquency, and adult adaptation. The presence of a learning disability is viewed as a risk factor that, in and of itself, does not predict positive or negative outcomes. Rather, other risk and protective factors, as highlighted in the literature, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
1
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 86 publications
4
118
1
6
Order By: Relevance
“…Huntington & Bender, 1993;Jensen et al, 1993;Prior et al, 1999;Cluver et al,2009) indicate the co-existence of anxiety, depression, post-traumatic stress or emotional problems on the one hand, and learning disabilities in children on the other. Rates of school drop-out, substance abuse and subsequent delinquency have also been found to be significantly higher in children with learning disabilities than in those without learning disabilities (Cameron & Dent, 2003;Morrison & Cosden, 1997). Therefore, the threat and potentially devastating impact of poverty not only encompass deprivation of resources, capabilities, choices, security and power necessary for the enjoyment of a satisfactory standard of living, but also extend across the physical, emotional and intellectual components of children's development.…”
Section: Introductionmentioning
confidence: 99%
“…Huntington & Bender, 1993;Jensen et al, 1993;Prior et al, 1999;Cluver et al,2009) indicate the co-existence of anxiety, depression, post-traumatic stress or emotional problems on the one hand, and learning disabilities in children on the other. Rates of school drop-out, substance abuse and subsequent delinquency have also been found to be significantly higher in children with learning disabilities than in those without learning disabilities (Cameron & Dent, 2003;Morrison & Cosden, 1997). Therefore, the threat and potentially devastating impact of poverty not only encompass deprivation of resources, capabilities, choices, security and power necessary for the enjoyment of a satisfactory standard of living, but also extend across the physical, emotional and intellectual components of children's development.…”
Section: Introductionmentioning
confidence: 99%
“…Children with learning disabilities frequently do not have accurate self-perceptions of their social competence. Morrison and Cosden (1997) found that the LD students' perspective of their disability had a major impact on their self-concept. A major factor in the adjustment to the learning disability was whether the students with LD perceived their learning disability as all-encompassing compared to students with LD who perceived learning disabilities as a discrete facet of their personal image.…”
Section: How Do Students With Learning Disabilities Perceive Themselvmentioning
confidence: 97%
“…A large body of research indicates that social skills difficulties may predict serious adjustment problems later in life (Bergman, 1987;Briney & Satcher, 1996;Court & Givon, 2003;Dawson, 2002;Dieffenbach, 1991;Dumas, 1998;Elksnin & Elsknin, 2001;Fuchs, Fuchs, Mathes, & Martinez, 2002;Goldstein, 2003;Gresham, Sugai, & Horner, 2001;Hayes, 1994;Jarvis & Justice, 1992;Koller & Goldberg, 2002;Lavoie, 1994;Levine, 1990;Lyon & Fletcher, 2001;McIntosh, 1989;Mellard & Hazel, 1992;Moisan, 1998;Morris, 2002;Morrison & Cosden, 1997;Noll, 1997;Peck, 1985;Rosenthal, 1992;Ross-Kidder, 1998;Rudolph & Luckner, 1991;San Miguel et al, 1996;Siegel, 1998;Steele, 1998;Sturomski, 1995;Tur-Kaspa & Bryan, 2002;Vacca, 2001;Vaughn, 1990;Vaughn & Haager, 1994;Vaughn & McIntosh, 1989;Vaughn, McIntosh, & Spencer-Rowe, 1991;Wheeler & Carlson, 1994;Woodward & Fergusson, 1999). Social interaction deficits are also a precursor for overall adjustment and functioning in society …”
Section: Delimitationsmentioning
confidence: 99%
“…Studies investigating the relationship between learning disabilities and violent offenses suggest a significantly higher proportion of juvenile delinquents with learning disabilities commit violent offenses (Blum et al, 2003). In this regard, researchers speculate that juveniles with learning disabilities demonstrate difficulties with impulse control and verbal mediation skills, and thus have more difficulty resisting involvement in delinquent acts, and may also be treated differently at the time of their arrest as a result of relative weaknesses in verbal mediation skills (Morrison & Cosden, 1997).…”
Section: Special Education Diagnosismentioning
confidence: 99%